An investigation into UK medical students' knowledge of lifestyle factors on cancer. Issue 3 (August 2017) - Luckman, S; Xiao, C; McLennan, E; Anderson, AS; Mutrie, N; Moug, SJ
Background and aim: Lifestyle factor modification (alcohol, smoking, obesity, diet, physical activity) has the potential to reduce cancer incidence and cancer survival. This study assessed the knowledge of lifestyle factors and cancer in undergraduate medical students. Methods and results: A total of 218 students (7 UK universities) completed an online survey of nine questions in three areas: knowledge (lifestyle factors and cancer); information sources; clinical practice (witnessed clinical counselling). Diet, alcohol, smoking and physical activity were recognised as lifestyle factors by 98% of responders, while only 69% reported weight. The links of lung cancer/smoking and alcohol/liver cancer were recognised by >90%, while only 10% reported weight or physical activity being linked to any cancer. University teaching on lifestyle factors and cancer was reported by 78%: 34% rating it good/very good. GPs were witnessed giving lifestyle advice by 85% of responders. Conclusions: Most respondents were aware of a relationship between lifestyle factors and cancer, mainly as a result of undergraduate teaching. Further work may widen the breadth of knowledge, and potentially improve primary and secondary cancer prevention.